Fidelity assessment of the suicide reporting guidelines in Korean newspapers - JongSerl Chun; Jinyung Kim; Serim Lee (BMC, 2018)
Abstract Background With the dishonor of being the highest suicide rated country in Organisation for Economic Co-operation and Development, South Korea should take more initiatives in suicide prevention. Although the role of the media and its relation to actual suicide attempts has been tested and supported by many studies, the suicide reporting guidelines are not well followed. The purpose of this study is to examine how well Korean newspapers adhere to existing guidelines and to suggest limitation and improvements for the current guidelines. Methods Five mainstream newspapers in South Korea, namely, Kyunghyang Shinmun, Hankyoreh, Chosun Ilbo, JoongAng Daily, and Dong-A Ilbo, were chosen for the analysis. Using the Naver news search engine, articles dated from January 1, 2014, to December 31, 2017, were selected with the keyword "suicide" and advanced option "printed newspaper." However, articles, columns, opinions, and reviews that utilized the word "suicide" in a general context were excluded from the final analysis. Finally, the number of cases was narrowed down to 368. Each article was analyzed using the guideline framework consisting of 13 items: sensational coverage, overstatement, direct wording, method used, details about site/location, photographs, suicide note, generalization, speculation, romanticization, interviews with the bereaved, help-seeking information, and public education. Results More than 60% of the articles included direct wording (63.9%), mentioned the method used (68.2%), and provided details about the site or location (74.5%). Nearly half of the articles revealed the contents of the suicide note (44.6%). Less than 3% of the suicide reports had information about hotline logo or phone numbers (1.4%) and facts regarding suicide and suicide prevention (2.2%). Conclusions Our study revealed that the guidelines were ineffective in their monitoring role and that most of the newspapers were incompliant with many significant guideline items in South Korea. Our findings not only explore the limitations of the current guidelines but also provide an important rationale as to why there should be stronger suicide monitoring regulation or an agency with sufficient authority to prevent suicide in a nation-wide scale.